The relationship between visual memory of non-words and accuracy and rate reading among female first-graders living in Isfahan-Iran - Nahid Baharlooie; Saghar GHolami; Maede SHariat; Mitra Nikzad (Vesnu Publications, 2011)
Abstract Introduction: Reading accuracy depends on such skills as normal hearing, auditory perception, auditory memory, normal visual perception and visual memory. The aim of this study was to determine the relationship between two reading skills, namely accuracy and rate of reading, and visual memory of non-words among female first-grade students living in Isfahan-Iran Materials and Methods: In a descriptive - analytic cross-sectional study, one-hundred female first-grade students were randomly selected from the available population. There was no evident sign of articulation, fluency, visual, auditory and intellectual problems in any of participants.  Each subject was first asked to read the test material while her reading performance was being recorded and then she underwent a visual memory test of non words. Finally through analyzing the recorded material, reading accuracy and rate scores were determined for all subjects. Results: according to the study's results, reading accuracy and visual memory were significantly correlated in first-graders (P=0/01). There was, however, no statistically significant relationship between rate of reading and visual memory in the studied population (P=0/614). A significant association was found between reading accuracy score and visual memory of non-words.   Conclusion: Visual memory is considered as a basic factor in development of reading skills. The results of this study are in agreement with those of other studies in that visual memory and visual recognition are more related to reading skills than any other cognitive skills. Therefore, by regard to the importance of relationship between visual memory and reading skills, visual memory should be tested in first-grade students. Key words: reading skill, reading accuracy, visual memory, non - word, rate of reading, first grade.